PERUMUSAN KONSEP CREATING SHARED VALUE (CSV) PADA PT. SEMEN INDONESIA GROUP DAN OBYEK PENELITIAN DI PT SEMEN GRESIK PABRIK REMBANG - Abdul Manan (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
Abstract: Along with the times, the paradigm of the realization of social and environmental responsibility must also have implications for the company's sustainability in the future, so it is necessary for companies to integrate economic interests and carry out social and environmental responsibilities, one of which is through Corporate Social Responsibility (CSR). The CSR that has been carried out by the company has indeed been running effectively and efficiently, but it is necessary to develop a strategy that can accommodate the obligation to carry out social and environmental responsibilities as well as related to economic interests in accordance with the company's strategy through Creating Shared Value (CSV) planning. This study aims to formulate the CSV concept at PT Semen Gresik, Rembang Factory. This type of research is phenomenology with a qualitative approach. Data collection techniques in this study were through in-depth interviews and Focus Group Discussions (FGD). In-depth interviews consisted of informants from internal companies and the public. Then for the FGD the sources were internal parties of PT Semen Gresik (2 people) and ring 1 community (2 people), as well as non-ring 1 community (2 people). The results of this study conclude that from several CSR programs that have been carried out by PT Semen Gresik, Rembang Factory, it is divided into 12 programs that can potentially be CSV programs. There are 4 CSV concepts formulated by the company, namely programs aimed at ring 1 and non ring 1 communities that are inline with short, medium and long term corporate strategies.Keywords: Creating Share Value (CSV), Continuity